Smart bracelet (i-Fit) / Norashikin Adam … [et al.] - Adam, Norashikin; Syed Nasir, Syed Faris; Abd Aziz, Farid Imran; Ahmad, Serhan; Mohd Yunus, Izzat Iliya Danish; Muhammad Nor Azam, Afiq Farhan; Azizi, Muhammad Akmal Rafiqin (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In Malaysia, it can be extremely difficult for people with disabilities (OKU) to maintain their safety and well-being, especially when it comes to keeping an eye on their health and making sure they get help quickly in an emergency. Current solutions frequently don't have the accessibility and integration needed to satisfy the wide range of needs of the OKU community. We have created a cutting-edge wearable gadget especially for the OKU community to address this problem. Presenting the "i-Fit," a multipurpose wristband with cutting-edge capabilities to improve OKU people's everyday life. Modern technology is included into the i-Fit, which has features like GPS tracking, fall detection, and real-time health monitoring. The device ensures timely assistance during crucial situations by continually monitoring vital signs and detecting falls. This allows for immediate alarms to be sent to caregivers or emergency services. Additionally, by giving OKU people the confidence to confidently navigate their environment and know that aid is readily available if needed, the i-Fit encourages independence and mobility. The configurable settings and intuitive interface of OKU enable users to meet a wide range of demands and preferences, enabling them to lead active and satisfying lives. Through the i-Fit, we aim to revolutionize the way OKU individuals experience safety, mobility, and peace of mind in Malaysia, fostering inclusivity and improving their overall quality of life.